Impressions from the International Days of Study (Fiep Bulletin - online, 2015)
The Decision to invite representatives of scientists working within the field of physiology, medical men and teachers with practical experience within the same field to a five day conference to discuss the problem “physical education for girls during the age of puberrty” must be given the greatest recognition. First and  foremost we must thank the organization.